Frontier markets in the banking industry : market analysis for a multi-channel bank willing to expand in emerging Asia - Lanza, Filippo (My University, 2015)
The banking industry has been one of the worst hit by the 2008-2009 global crisis, a situation further complicated by the introduction of tougher regulations and by increasing compliance costs. In order to return to profitability, it is important that banks strive to find new opportunities of growth, also by searching new markets abroad. As Asian emerging markets become richer, the demand for more sophisticated financial services is still partially untapped and, therefore, may represent a potentially good opportunity for foreign banks willing to take the risk. Despite emerging Asia is one of the fastest growing areas for smartphones adoption and increase of internet connections, local banks are still operating mainly in the traditional, physical way. Therefore, the introduction of digital banking practices may become a breakthrough business model, enabling foreign banks to better stand local competition. This study, by leveraging on an exploratory case study, aims to uncover the latent opportunities in developing Asian countries for a multi-channel bank. The analysis will be based on secondary data gathered from different sources, like: international organizations, statistical institutions and reports issued by consulting companies. Despite some small adjustments, the Market-screening model suggested by Cavusgil, Knight, Riesenberger & Yaprak (2009) has proven useful and easy to implement for a company willing to exploit latent opportunities in foreign markets. By applying this framework, the results point out that China is the optimal market for the case company to start its expansion in emerging Asian countries. Therefore, most of the market analysis will be focused on the Chinese economy and the local banking industry. Findings suggest that the Chinese banking industry, while posing major challenges to foreign players, it is also rapidly developing towards a more sophisticated competitive environment. By coupling a niche strategy with the cost benefits of a digital offering, foreign banks can effectively compete (even though at a smaller scale) with most of their Chinese competitors. Moreover, this study supports the hypothesis that foreign market selection and analysis can be performed, at least at a preliminary stage, by relying on secondary data, easily available at relatively low costs.
Keywords: Market Analysis; Banking Industry; Emerging Asian Markets; China.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|